C clustering and partitioning by static strain aging in cold-rolled 16Cr-5Ni supermartensitic stainless steel. (February 2021) - Gwon, Hojun; Kim, Sung-Ho; Jeon, Jong Jin; Kim, Sung-Joon
Abstract: Static strain aging behavior of cold-rolled 16Cr-5Ni supermartensitic stainless steel was investigated after it had been aged for 30 min at 400°C. In uniaxial tensile tests of 20% cold-rolled specimens, increase of yield strength to ~300 MPa and decrease of strain hardening rate were observed in the aged specimen, compared to the as-rolled specimen. In interrupted tensile tests, delayed martensitic transformation was observed in the aged specimen. Dilatometry analysis detected volume shrinkage during the 30 min holding period at 400°C indicating partitioning of carbon (C) from α' martensite to austenite. The clustering of C in α' martensite was confirmed by impulse internal friction technique with observation of Cottrell atmosphere formation. 3D atom probe tomography analysis revealed partitioning of C atoms into austenite and clustering of C atoms in the α' martensite. The remarkable increase of yield strength was attributed to redistribution of C atoms during the aging treatment. Graphical Abstract: Image, graphical abstract